Synthetic Gene-Based Heterologous Expression, Proteolytic, and Structural Characterization of Caseinolytic Protease of Lactobacillus plantarum IIA-1A5 - M. Yusuf; C. Budiman; I. I. Arief; C. Sumantri (Tropical Animal Science Journal, 2021)
Genome sequence of Indonesian probiotic of Lactobacillus plantarum II1A5 contains a gene encoding a proteolytic subunit of caseinolytic protease, designated as ClpP_LP. This study aims to express the Clp gene heterological and apply its proteolytic activity to some livestock products. To address this, the gene encoding ClpP_LP was optimized in silico by improving its Codon Adaptation Index and GC content to 0.94 and 53.62%, respectively. The optimized gene was then inserted into pET28a, transformed into Escherichia coli BL21(DE3), and over-expressed by induction of 1 mM Isopropyl β-D-1-thiogalactopyranoside at 37°C. The result showed that ClpP_LP was successfully over-expressed in a fully soluble form with the specific activity towards milk casein was 7739.89 AU mg-1. This activity was significantly greater than that of chymotrypsin. Further, the three-dimensional model of ClpP_LP was built using SWISS MODEL, which showed that this protein formed a homo-tetradecameric (14-mer) structure with each monomer consisting of 7 α-helix and 10 β-sheets. The identification of the active side showed that the active side of ClpP_LP is Ser-97, His-122, Asp-171, and forms a substrate-binding cavity with a size of about 29.5 Ǻ. Overall, our approach can serve as an appropriate platform for the production of ClpP_LP in a large-scale production for various applications in dairy products and derivatives.